Ruas completas: estratégias para desenhos urbanos em cidades de pequeno porte - Faleiro, Tailini da Silva Caminha (Universidade do Vale do Rio dos Sinos, 2024)
New needs arise at all times with regard to the use of public space and, therefore, new possibilities for urban designs emerge. With the encouragement of car use, the urbanization process seems to have prioritized the flow of vehicles to the detriment of space dedicated to people. One of the ways to encourage people to experience public spaces is to provide conditions for people to feel comfortable, safe and invited to frequent them. This type of initiative has been growing and, in consequence, new topics have been incorporated into the discussions. One of them is the concept of complete streets. In this scenario, the research studies which variables linked to the concept of complete streets can contribute to obtaining safer and more attractive urban designs focusing on small cities, as traveling with accessibility and safety is everyone's right, although the majority of existing cases include larger cities. Hence, the town of Taquari/RS was selected as a case study. In methodological terms, the discussion is carried out in four stages. The first stage is composed of bibliographical research, focused on the evolution of cities and urban centers, and documentary research, aiming to contextualization with the development of Taquari, through files, maps and municipal laws, ending the conceptual theoretical stage. The second stage consists of the study of national and international projects for complete streets, where the main variables used were identified. The third stage presents the case study, in which two streets from the base town were selected, which were analyzed through data collection and on-site observation. And, the fourth stage, is made up of the comparison between the variables most used in complete street projects and the analysis carried out through the field study. As a result, the research contributes to a manual, which presents criteria for choosing variables that apply to small cities, with the aim of disseminating the concept in other cities or similar contexts.
Keywords: Desenho urbano; Pedestre; Mobilidade ativa; Ruas completas; Urban design; Pedestrian; Active mobility; Complete streets; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo